Representações do ensino da leitura: as aulas de português na escola secundária brasileira (séculos XIX e XX) - Medeiros, Rejane Rodrigues Almeida de (Universidade Federal de São Carlos, 2019)
The literary reading seems to have achieved a central role by the activities of teaching Portuguese Language at the end of 19th century and the first decades of 20th century, acting as a starting point for the development the ability of reading aloud or in silence, the learning of grammatical rules, the moral education, the acquisition of knowledge about literature, the education of literary taste, as well as for the elaboration of writing skills. The main purpose of this thesis is to deduce, through the analyses of Portuguese school textbooks and articles from teaching magazines published between 1890 and 1970 the forms of representation of teaching practices in the Portuguese classes of Brazilian secondary school in XIX and XX centuries, until the 1960 decade, the period in which literary reading prevailed in the class room. The corpus researched is constituted by anthologies, Portuguese books and textbooks from the Portuguese teacher, such as Seleta clássica (1914, 3ª ed.), from João Ribeiro; Céu, terra e mar (1920, 4ª ed.), from Antonio Mariano Alberto de Oliveira; Antologia Nacional (1929, 14ª ed.), from Fausto Barreto e Carlos Laet; O idioma nacional na escola secundária (1935) and O idioma nacional (1944), antologias para o ginásio e colégio, from Antenor Nascentes; the didactic series Livro de Português (1935-1955), from Magda Soares; and from teaching magazines, such as Revista Pedagógica (1890-1896), edited by the Union in Rio de Janeiro, and the Revista de Educação (1927-1961) published by the Education Secretary of the State of São Paulo. The theoretical and methodological referential adopted for the analyses of the described corpus is composed by the cultural history of reading in dialogue with the works about the history of Portuguese Language teaching in secondary school, as well as researches on the history of education. Besides presenting certain variation according to the goals by which the literary reading teaching is subject in the school, the representation forms of reading teaching in secondary school in the period analyzed also vary according to the historical and social conditions from which they emerged, what means that it is possible to realize, in the materiality and in the discourses from didact texts some continuities as well as disruptions with the practices of the past.
Keywords: História do ensino da leitura; História do ensino de língua portuguesa; História da disciplina escolar Português; História Cultural da Leitura; History of teaching reading; History of the Portuguese language teaching; History of the school subject Portuguese; Cultural history of reading; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUA PORTUGUESA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA